(untitled) (African Journal of Dairy Farming and Milk Production, 2016)
Impact of negative energy balance (NEB) and its consequences on milk production and reproduction were studied in 51 dairy cows. All cows were randomly selected from 11 small-holder farms according to their calving date during December 2006 to May 2007. Body condition score and milk yield were recorded. Blood samples were collected from all cows at 2 weeks before expected calving date and at 2 and 4 weeks after calving to determine glucose, nonesterifed fatty acids, triacylglycerol, cholesterol and urea nitrogen concentrations. Postpartum reproductive activities were also recorded. Results showed that dairy cows in this study had significantly lower serum glucose and triacylglycerol, and significantly higher serum of non-esterified fatty acids concentrations after parturition. Cows also lost their weights during postpartum period as compared with prepartum period. Results indicated that these cows suffered from NEB. The average milk yields during 16 weeks of lactation did not show the peak of yield. Pregnancy rates of these cows were 28.6, 11.1, and 12.0% for first, second, and third artificial insemination. In conclusion, these dairy cows went into a periparturient NEB period, and its consequences on suboptimal milk yields and lower conception rates were observed. Prevention of the adverse effects of NEB and its consequences would result in an increase of performance of dairy cows raised in small-holder farms.